Foursquare - Amaral, Inês (2015)
Foursquare is a location-based social media service that provides users with a personalized local search experience. As a geo-location application, Foursquare uses the global positioning system in mobile devices to generate locations and provide a list of places. “Check-in” is the process of identifying the user’s location. The platform is based on the idea that people can use mobile devices to interact with their environment, and it aims to provide recommendations of the best places around a user’s current location. Dennis Crowley and Naveen Selvadurai launched the service in 2009 at the South by Southwest Interactive conference. Foursquare was based on Dodgeball, Crowley’s graduation project. In this platform, users sent their location by text message and received information about friends who were close by.